Person-centred care for dementia patients (front-end system development) - Tan, Josephine Wei Lin (Nanyang Technological University, 2020)
Dementia is a condition that affects the brain which causes the decline in intellectual abilities such as memory, reasoning skills etc. One of the significant factors associated with dementia is older age. This means that the rapid increase in population aging faced by Singapore, will result in the major increase in the number of dementia patients as the years go. The PEAR system was developed to provide better assistance to caregivers. The system would provide the best quality of Person-centred care which not only alleviate stress in caregivers, but also to provide high-quality person-centred care is delivered to the dementia patients. The application also caters to different user needs as each of them have different priorities. Users can also view vitals, schedules and other important health information of the patients which are updated in real time to aid in providing quality care to dementia patients and also help in decision making. The objective of this project is to revamp the PEAR mobile application, achieve consistency and Extend any missing core functionalities. The features in the PEAR mobile application must be consistent with the ones in PEAR website. Essential features and functionalities will be identified, amended so that it performs as what it is like in PEAR website. This helps to improve user experience by extending the missing feature in application. Throughout the course of the project, the author had implemented the Holiday Experience page and the photo album page. These pages handle photos that are personal to the patient. Quality attributes like usability and simplicity are fulfilled. The details of each page are retrieved using API call and validation are also done to ensure data sent is correct.